Association Between Irritable Bowel Syndrome and Burn Out in Post Graduate Trainees of Allied Hospitals of RMU: A Cross-Sectional Study - Faryha Aslam, Ayesha Hassan (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
INTRODUCTION: Healthcare professionals, especially postgraduate trainees, are vulnerable to burnout due to their busy work schedules, frequent on-calls, lack of sleep and emotional stress, which can lead to IBS. OBJECTIVES: To determine the frequency of IBS-related symptoms. To assess the degree and intensity of burnout. To determine the IBS subtype. To investigate professional and demographic factors linked to burnout and IBS. Methods: This descriptive cross-sectional study was conducted over a period of three months among postgraduate trainees at RMU and its allied hospitals. A total of 29 participants were recruited using non-probability consecutive sampling. Postgraduate residents of RMU and allied institutions were included, while individuals diagnosed with inflammatory bowel disease, other gastrointestinal disorders, or depression, as well as residents on rotation outside RMU, house officers, and exam-going residents, were excluded. Data collection tools included the 28-item Burnout Questionnaire developed by the American Welfare Association and the WGO “IBS Questionnaire for Healthcare Providers,” along with the ROME IV criteria for diagnosing irritable bowel syndrome and the Bristol Stool Form Scale for subtype classification. Statistical analysis was performed using SPSS version 25. Descriptive statistics were applied to summarise demographic variables, and chi-square testing was used to assess the association between burnout and IBS. Mean burnout scores of IBS-positive and IBS-negative participants were compared using independent t-tests. Receiver operating characteristic (ROC) curve analysis was performed to identify a burnout score cutoff predictive of IBS, along with corresponding sensitivity and specificity values. RESULTS: The mean burnout score was 68.90 ± 24.78, while the mean WGO IBS score was 35.21 ± 5.12. ROC curve analysis demonstrated that a burnout score of ≥46.50 predicted the presence of IBS with 80% sensitivity and 80% specificity, suggesting a strong association between burnout and IBS in this population. CONCLUSION: There is a significant association between IBS and burnout among postgraduate residents of allied hospitals of RMU KEYWORDS: Irritable Bowel Syndrome, Burnout